Ключевые работы ученых НТУ "ХПИ" в области математического моделирования в технике - Назаренко, Сергей Александрович; Марусенко, Светлана Ивановна (НТУ "ХПИ", 2015)
Статья посвящена рассмотрению эволюции в 19 – 21 столетиях основных научно–педагогических достижений ученых и выпускников НТУ «ХПИ» в области математического моделирования: от паровых машин до космических аппаратов. Начало украинской науки в области математического моделирования в технике и технологиях связано с НТУ «ХПИ». Здесь работали или учились В. Л. Кирпичев, А. М. Ляпунов, В. А. Стеклов, Л. Д. Ландау, А. Н. Подгорный, Ю. М. Мацевитый и др. Ученые НТУ «ХПИ» создавали космическую и турбокомпрессорную технику, ЭВМ и термоядерные установки, и т. д. Показано, как математизация исследовательской деятельности привела к появлению новых методик анализа и синтеза в технике и технологиях.

The paper is concerned with the dynamic process of establishment and development of the research and pedagogic activity of the scientists and graduates of the National Technical University «Kharkiv Polytechnic Institute» (NTU «KhPI») in the field of mathematical modeling in engineering and technologies in the 19 – 21 centuries. The beginning of the Ukrainian technical science in the field of mathematical modeling in engineering and technologies is associated with the NTU «KhPI». The range of scientific designs created in the NTU «KhPI» varies from specific space products to a number of “common” products for the needs of machinery, power production, etc. The fundamental scientific trends of evolution of mathematical modeling in engineering and technological processes were discovered and explored here. The most important phases of formation and development of the research and design school of the NTU «KhPI» are shown. The world-famous scientists who worked at the NTU «KhPI» or graduated it are mentioned.
Main achievements of scientists of NTU "KhPI" in the field of mathematical modeling in engineering
Keywords: механика; технология; динамика; mechanics; mathematical model; engineering; technology; dynamics; design